2018
DOI: 10.1159/000495879
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α Signaling in the Endogenous Protective Responses after Neonatal Brain Hypoxia-Ischemia

Abstract: Hypoxia-inducible factor 1α (HIF1α) is a key regulator of oxygen homeostasis, and its target genes mediate adaptive, protective, and pathological processes. The role of HIF1α in neuronal survival is controversial and the brain maturation stage is important in determining its function in brain ischemia or hypoxia-ischemia (HI). In this study, we used neuronspecific HIF1α knockout mice at postnatal day 9 (P9), and immature cortical neurons (days 7-8 in vitro) treated with the HIF1α inhibitor 2-methoxyestradiol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Our findings that the expression of the transcription factor hypoxia-inducible factor 1α (HIF-1α) increases after a hypoxia-ischemia insult supports that cerebellar primary neurons are responsive to the injury conditions and are consistent with previous studies, both in vivo and in vitro, showing that mouse cortical neurons exposed to hypoxic conditions showed an increase in this factor [ 32 , 33 , 34 ]. It is well known that the increase of HIF-1α is a characteristic response of cells to hypoxia and ischemia during early development [ 35 , 36 ], which could be associated with its neuroprotective effects [ 37 ], although it has also been described that the increase has neurotoxic effects [ 38 , 39 ]. Our results show that cell viability decreased after exposure to hypoxia-ischemia and reoxygenation while cell death parameters (apoptosis and necrosis) increased, which suggests that the intrinsic factors of primary cerebellar neurons are not sufficient to decrease the cell damage progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings that the expression of the transcription factor hypoxia-inducible factor 1α (HIF-1α) increases after a hypoxia-ischemia insult supports that cerebellar primary neurons are responsive to the injury conditions and are consistent with previous studies, both in vivo and in vitro, showing that mouse cortical neurons exposed to hypoxic conditions showed an increase in this factor [ 32 , 33 , 34 ]. It is well known that the increase of HIF-1α is a characteristic response of cells to hypoxia and ischemia during early development [ 35 , 36 ], which could be associated with its neuroprotective effects [ 37 ], although it has also been described that the increase has neurotoxic effects [ 38 , 39 ]. Our results show that cell viability decreased after exposure to hypoxia-ischemia and reoxygenation while cell death parameters (apoptosis and necrosis) increased, which suggests that the intrinsic factors of primary cerebellar neurons are not sufficient to decrease the cell damage progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is yet to be determined how APAP exposure effects developing human neurons in vivo, but prior studies have demonstrated effects on transformed neuronal stem cell lines in vitro utilizing toxic concentrations. HIF1α signaling ( Table 2 ) has a role in the development of sympathetic ganglion neurons and is known to regulate genes that are involved in adaptive and protective neuronal processes during maturation [ 55 , 56 ]. In mice, genetic deletion of HIF1α leads to increased cell death and decreased proliferation of neuronal progenitor cells within the sympathetic nervous system [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, genetic deletion of HIF1α leads to increased cell death and decreased proliferation of neuronal progenitor cells within the sympathetic nervous system [ 55 ]. Another mouse model also showed that inhibition or deletion of neuronal HIF1α increased necrotic and apoptotic cell death [ 56 ]. After exposing pregnant rats to glyphosate-based herbicides, one study found offspring to exhibit significant increases (73%, p = 0.017) in HIF1α in the cerebellum [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Shi et al [45] found that the severity of cerebral ischemia acted differently on Sestrin2 expression levels. Sestrin2 is significantly induced by HIF-1α in severe cerebral ischemia and inhibits VEGF to reduce the permeability of blood-brain barrier (BBB), which reduces the occurrence of cerebral edema and hemorrhagic cerebral infarction [45][46][47]. Taken together, Sestrin2 plays a significant role in cerebral hypoxic disease, it may serve as a potential therapeutic target for brain I/R injury.…”
Section: Sestrin2 and Cerebral Hypoxic Diseasementioning
confidence: 99%